A review of biomarkers for predicting clinical reactivity to foods with a focus on specific immunoglobulin E antibodies. Issue 3 (June 2015) - Sato, Sakura; Yanagida, Noriyuki; Ohtani, Kiyotaka; Koike, Yumi; Ebisawa, Motohiro
Abstract : Purpose of review: The purpose of this study is to assess the latest studies that focus on specific immunoglobulin (Ig)E antibodies for predicting clinical reactivity to foods. Recent findings: Persistent hen's egg and cow's milk allergy patients have higher antigen-specific IgE levels at all ages than those who have outgrown these allergies. Recent studies on the natural histories of hen's egg and cow's milk allergies suggested that baseline antigen-specific IgEs are the most important predictors of tolerance. Oral immunotherapy (OIT), which is a novel therapeutic approach for food allergy, requires biomarkers for predicting outcomes after therapy. Several studies indicate that the initial antigen-specific IgE level may be a useful biomarker for the prognosis of OIT. Recently, component-resolved diagnostics (CRD) has been used for food allergy diagnosis. Current studies have suggested that Ara h 2, omega-5 gliadin and ovomucoid are good diagnostic markers for peanut, wheat and egg allergies, respectively. Summary: Antigen-specific IgE can be a useful biomarker for predicting clinical reactivity to food allergies. Monitoring hen's egg and cow's milk-specific IgE is useful for predicting prognosis, and baseline specific IgE levels may be associated with the outcome of OIT. The use of CRD provides us with a better tool for diagnosing food allergy.